Prinsip Induksi Matematika dalam Pengambilan Keputusan Organisasi - Atmaja, I Made Dharma (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The principle of mathematical induction can be an effective tool in organizational decision making. Although these principles have the potential to increase efficiency, reduce uncertainty, and increase accuracy in organizational decision making, their application is limited and has not been fully exploited. Studies need to be conducted to bridge this gap by strengthening the understanding and application of the principles of mathematical induction in the context of organizational decision making. By considering the gaps that occur, it is necessary to conduct research on